2018
DOI: 10.1161/circulationaha.117.032617
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Prognosis of Cancer After Lower Limb Arterial Thrombosis

Abstract: Lower limb arterial thrombosis was a marker of occult cancer, especially lung cancer, and was an adverse prognostic factor for mortality in common cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Sundboll and colleagues examined cancer risk and prognosis of cancer in patients with lower limb PAD and arterial thrombosis. They reported that the risk of any cancer was 2.5% after 6 months of follow-up, which increased to 17.9% after 20 years [ 65 ]. Since cigarette smoking happens to be the common risk factor for many cancers, such as cancer of lung, head and neck, esophagus, stomach, liver, colon, pancreas, kidney, bladder, ovary, uterine cervix and myeloid leukemia, the association of PAD can be an indirect evidence of presence of cancer and overall influence on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Sundboll and colleagues examined cancer risk and prognosis of cancer in patients with lower limb PAD and arterial thrombosis. They reported that the risk of any cancer was 2.5% after 6 months of follow-up, which increased to 17.9% after 20 years [ 65 ]. Since cigarette smoking happens to be the common risk factor for many cancers, such as cancer of lung, head and neck, esophagus, stomach, liver, colon, pancreas, kidney, bladder, ovary, uterine cervix and myeloid leukemia, the association of PAD can be an indirect evidence of presence of cancer and overall influence on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the risk of cancer in patients with arterial embolism was 2.5% after 6 months and 17.9% after 20 years of follow-up. 9 The development of both venous and arterial thromboembolism should raise the suspicion of underlying pathology even more, but descriptive data on the incidence rate of malignancy in this situation are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial thromboembolism was once thought to be quite rare, but the reported rate varies between 11.7% of critical limb ischemia patients 5 and 16% of all acute limb ischemia with occult malignancy. 6 It can present with cardiac, splenic, and renal infarcts, as well as ischemic strokes 7 and vessel occlusion in either upper or lower limbs.…”
Section: Discussionmentioning
confidence: 99%